EFFICACY OF TREATMENT OF LOWER EXTREMITIES DEEP VEIN THROMBOSIS WITH DIFFERENT EXTEND USING MODERN ORAL ANTICOAGULANTS - B. S. Sukovatykh; M. B. Sukovatykh; V. F. Muradyan; A. V. Sereditskiy; A. M. Asarov; O. A. Rodionov; O. F. Gerasimova; А. A. Lapinas (Вестник хирургии имени И.И. Грекова)
The objective is to assess the efficacy of rivaroxabane and dabigatran etaxilate in treatment of the deep vein thrombosis with different extend.Material and methods. The analysis of complex examination and treatment of 120 patients with venous thromboembolism was accomplished. All patients were randomized into two groups; each group consisted of 60 patients. The first group started the therapy with 5-days course of unfractionated heparin and followed the therapy with 6-month course of dabigatran etaxilate. Patients of the second group were treated only with rivaroxabane for 6 months.Results. The treatment was over the full restoration of the lumen of thrombosed veins in 46.7 %. Venous stenosis was registered in 34.2 %, and venous occlusion detected in 19.1 %. The efficacy of dabigatran etexilat and rivaroxabane was similar in local and diffuse thrombosis. Whereas dabigatran etaxilate was more effective in treatment of total and subtotal thrombosis. Сhronic venous insufficiency was absent in 35 % of patients, was mild degree in 43.3 % of patients, moderate degree in 10,8 % of patients, and severe degree in 10,8 % of patients. Moderate and severe degrees of chronic venous insufficiency were less common in 7.7 % of patients treated with dabigatran etaxilate.Conclusion. Anticoagulant therapy with rivaroxabane is advisable in local and diffuse thrombosis; treatment of total and subtotal thrombosis is advisable to start with 5-days course of unfractionated heparin.